A Pengelolaan Dana Sosial Masyarakat Dalam Meningkatkan Kualitas Sumber Daya Manusia Masyarakat Jampang, Bogor - S. Haratua, Chandra; Ilham Syahroni, Muhamad; Marlina, Iin; Ridwan, Muhamad (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2023)
This study aims to assess the management of social funds for the people of Jampang, Bogor to determine the achievement of program impact performance with parameters of changes to assets/capital in an effort to increase human resources and then to find out the fundamental changes experienced by the target community. Research methodology-Using a research method, namely the SLIA (Sustainable Livelihood Impact Assessment) method, to measure changes in community assets before and after the program. Change data is the result of acknowledgment from respondents obtained from in-depth interviews, questionnaires and. Practical Implications-The results of this study are used to measure the impact analysis of community social fund management programs